1998
DOI: 10.1159/000029021
|View full text |Cite
|
Sign up to set email alerts
|

Treated versus Untreated Major Depressive Episodes

Abstract: It is a plausible hypothesis that among treated cases of major depressive episodes (MDE) in the community, females will be overrepresented, episodes will be more severe, the course of the disorder will be more frequently chronic and the consequences in the depression more serious. This hypothesis was tested on the subjects of the Zürich cohort study, an enriched population sample (n = 591), which was examined 5 times between the ages of 20 and 35. We found a longitudinal prevalence rate for MDE of 20.2% (13.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
5
10
0
Order By: Relevance
“…However, if the severity of depression as measured by HAM-D is excluded, the MMPI effects become weaker but remain significant and to our surprise MPI neuroticism becomes predictive of unfavorable 1-year course. This result fits in nicely with those of Angst et al [31] and Marneros et al [32] who also found that the pre-index course and personality are the main factors influencing short-term course.…”
Section: Discussionsupporting
confidence: 91%
“…However, if the severity of depression as measured by HAM-D is excluded, the MMPI effects become weaker but remain significant and to our surprise MPI neuroticism becomes predictive of unfavorable 1-year course. This result fits in nicely with those of Angst et al [31] and Marneros et al [32] who also found that the pre-index course and personality are the main factors influencing short-term course.…”
Section: Discussionsupporting
confidence: 91%
“…The lifetime treatment rate of individuals with a lifetime diagnosis of MDD (32.3%) were lower than the results of most community-based surveys in Western countries using a time span of 12 months except the only one study (Kessler et al 1999); for example rates of 57.3% were reported in American population (Kessler et al 2003), 48.0% in Canadian population (Wang 2004), 45.3% in the Netherlands (Spijker et al 2001), and 38.0% in Switzerland (Angst 1998). This rate was also much lower than the (Ma et al 2009).…”
Section: Discussionmentioning
confidence: 60%
“…Some of the discrepancies across studies may be related to differences in the diagnostic criteria of MDD, the study period or the definition of treatment. Several previous studies used DSM-III-R criteria (Angst 1998;Galbaud du Fort et al 1999;Kessler et al 1999;Spijker et al 2001), whereas others (Kessler et al 2003;Wang 2004), including ours used DSM-IV criteria to diagnose MDD. Moreover, the recent growth in the medical service market may have affected the differences in treatment rates between older and more recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations